ADIPONECTIN, RESISTIN AND HORMONE-METABOLIC PARAMETERS IN MEN WITH HYPOTHYROIDISM AND TYPE 2 DIABETES MELLITUS - Вербовой, Андрей Феликсович; Ломонова, Татьяна Владимировна (Medicine in Kuzbass, 2018)
Aim – assess the relationship between adiponectin, resistin and hormone-metabolic parameters in men with hypothyroidism and type 2 diabetes mellitus.Materials and methods. The study involved 62 men aged from 36 to 72 years, who were divided into 2 groups. The first group included 14 men with hypothyroidism, whose median age was 54.00 years [43.00; 60.25]. The second group consisted of 48 patients with type 2 diabetes whose mean age was 57.00 years [50.25; 62.00]. The control was the results of examination of 60 practically healthy men: 30 men with an average age of 21.00 years [20.00; 21.00] and 30 men at the age of 54.00 years [51.00; 56.00]. All patients underwent anthropometric examination. For all patients were studied levels of glucose, immunoreactive insulin, adiponectin, resistin, the lipid profile was assessed. The index of insulin resistance HOMA-IR was calculated.Results. There were revealed hyperglycemia, hyperinsulinemia and insulin resistance in men with type 2 diabetes. In patients with hypothyroidism, hyperinsulinemia is established against the background of increased insulin resistance. All patients had elevated levels of total cholesterol and triglycerides, and adiponectin concentration is decreased.The level of resistin in patients with hypothyroidism and type 2 diabetes was not different from control groups.Conclusion. In men with type 2 diabetes mellitus, compensatory hyperinsulinemia is detected on the background of insulin resistance. There were revealed increased insulin resistance and hyperinsulinemia in men with hypothyroidism. In patients with type 2 diabetes mellitus and hypothyroidism, atherogenic dyslipidemia and hypoadiponectinemia have been identified. Hypoadiponectinemia takes part in the development of insulin resistance in hypothyroidism.
Keywords: type 2 diabetes mellitus; hypothyroidism; insulin resistance; adiponectin; resistin; men